Strategies for Improving Employee Performance Through Strengthening Organizational Culture, Work Discipline, Training Programs and Trust - Kustini, Endang; Yusnita, Nancy; Sunaryo, Widodo (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This study aims to test the influence of organizational culture, work discipline and training programs on employee performance with trust as a mediator. Methodology/approach – The population in this study were all civil servants in functional positions at the Ministry of Cooperatives and SMEs of the Republic of Indonesia totaling 253 employees. The sampling technique used proportional random sampling with the Slovin formula with an error margin of 5% with a sample size of 155 respondents. The data analysis method used in this study was Path Analysis. Findings – There is a significant positive direct influence of Organizational Culture, Work Discipline, Training Programs and Trust on Employee Performance. There is a significant positive direct influence of Organizational Culture, Work Discipline, and Training Programs on Trust. The Trust variable is able to mediate the influence of Organizational Culture, Work Discipline, and Training Programs on Employee Performance. Novelty/value – This study raises a topic that has been relatively little explored in the context of improving employee performance in the government sector, especially in the Ministry of Cooperatives and SMEs of the Republic of Indonesia, with a focus on Civil Servants in Functional Positions.